Strategi pembinaan pelanggar hukum dalam konteks penegakan hukum di Indonesia - Atmasasmita, Romli, 1944- (Alumni, 1982)
On the process of resocialization of prisoners, with special reference to criminal justice system and law enforcement in Indonesia.